2016
DOI: 10.1016/j.hpb.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy (SBRT) with or without surgery for primary and metastatic liver tumors

Abstract: In this retrospective analysis we demonstrate that liver SBRT alone or in combination with surgery is safe and effective for the treatment of isolated inoperable hepatic malignancies and provides excellent local control rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Twenty-two of the 38 patients utilized 4DCT co-registered with 99mTc-sulfur colloid Single Photon Emission Computed Tomography (SPECT) for visualization and conformal avoidance of best perfused hepatic parenchyma. Details of SPECT/CT co-registration and treatment planning have been previously reported for liver SBRT in cirrhotic HCC patients[ 19 , 20 ]. Dose limits were set such that at least 35% of predicted liver volume by SPECT imaging received ≤ 18 Gy in 5 fractions or ≤ 16 Gy in 4 fractions.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-two of the 38 patients utilized 4DCT co-registered with 99mTc-sulfur colloid Single Photon Emission Computed Tomography (SPECT) for visualization and conformal avoidance of best perfused hepatic parenchyma. Details of SPECT/CT co-registration and treatment planning have been previously reported for liver SBRT in cirrhotic HCC patients[ 19 , 20 ]. Dose limits were set such that at least 35% of predicted liver volume by SPECT imaging received ≤ 18 Gy in 5 fractions or ≤ 16 Gy in 4 fractions.…”
Section: Methodsmentioning
confidence: 99%
“…In one retrospective study using 99m Tc-sulfur colloid SPECT-CT into the treatment planning process to avoid functional areas of the liver, the investigators observed no incidence of RILD, grade 3 or higher hepatic toxicity, or accelerated liver failure in HCC patients with advanced cirrhosis who completed liver SBRT 50, 51 . The outcomes in these studies are similar to prospective trials evaluating SBRT in HCC without functional treatment planning, where the incidence of grade 3 or higher hepatotoxicity ranged between 5% - 36% 7, 52, 53 .…”
Section: Functional Liver Imaging and Incorporation Into Radiation Plmentioning
confidence: 99%
“…There is also an increasing evidence base/clinical experience for the use of SABR in other primary cancer sites such as the prostate, pancreas, liver (metastases and primary hepatocellular carcinoma) and spinal metastases, and for oligometastatic disease. [4][5][6][7][8][9] In order to deliver ablative doses of RT to tumours, it is necessary to accurately identify both the target and the surrounding organs at risk (OARs), in addition to accommodating inter-and intrafraction movement of both. 10 The three key components required to achieve this involve patient immobilization, on-treatment image guidance and ontreatment patient motion management.…”
Section: Introductionmentioning
confidence: 99%